Real Time Clock Sebagai Tracking Sinar Matahari Pada Solar Cell Berbasis Mikrokontroler Untuk Lampu Taman - Moch Nur Qomaruddin; Matlubul Khairi (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2019)
One of the new and renewable energy is the utilization of sunlight into electricity. which can be used to be converted into electrical energy using solar panels. Installation of solar panels that are installed for garden lights so far are often still placed in a static position (silent) at an angle of 90⁰, while the sun moves from sunrise to sunset. Because it will cause maximum energy absorption in solar panels placed in a static position only at12:00. To overcome this problem a system is needed to track the position of the sun so that it is always perpendicular to the surface of the solar panel. Design and build Garden lights with a solar light tracking system on a microcontroller-based solar panel will later be made to move as it follows the direction of the sun's movement every hour, from sunrise to sunset. This tool will detect the time setting inputted by Real Time Clock (RTC) which is then processed by a microcontroller to drive a servo motor that functions as a solar panel drive machine so that the position of the solar panel will always be perpendicular to the sun throughout the day and the absorption of energy in the solar panel will more leverage. From the results of tests that have been done, the increase in the voltage of solar panels using a tracking system compared to solar panels without using a tracking system is 7.85%.